2014
DOI: 10.1111/ejss.12126
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the impacts of maize decomposition on glyphosate dynamics in mulch

Abstract: The retention of crop residues as mulch on the soil surface in conservation agriculture systems greatly influences the fate of pesticides, as most of the applied pesticide is intercepted by mulch before moving to the soil. This work was conducted in order to model the effect of maize decomposition on glyphosate degradation in mulch and soil. Labelled 14 C-glyphosate degradation was monitored for 49 days in three treatments with the same soils but with maize residues at different stages of decomposition (0, 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Using 14 C labelled glyphosate, the authors have recently quantified strongly sorbed (extracted by NH 4 OH) and non‐extractable residues in similar experimental systems but without rainfall conditions. At day 0, both fractions represented more than 40% of initial applied glyphosate, with the majority being found in soil below the mulch . This could explain the much lower mass recovery of glyphosate (54%) compared with S ‐metolachlor (89%) at the beginning of the incubation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using 14 C labelled glyphosate, the authors have recently quantified strongly sorbed (extracted by NH 4 OH) and non‐extractable residues in similar experimental systems but without rainfall conditions. At day 0, both fractions represented more than 40% of initial applied glyphosate, with the majority being found in soil below the mulch . This could explain the much lower mass recovery of glyphosate (54%) compared with S ‐metolachlor (89%) at the beginning of the incubation.…”
Section: Resultsmentioning
confidence: 99%
“…The interpretation of the glyphosate data is more difficult owing to the difficulties encountered in establishing satisfactory mass recoveries. As previously mentioned, the extraction procedure (water and sonication) did not allow for the recovery of all glyphosate in the soil because of the strong adsorption of glyphosate to soil . In addition, the quantification and detection limits of glyphosate were much greater than those of S ‐metolachlor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aslam et al (2013) suggested that the adsorption of pesticides was associated with the chemical composition of crop residues. The characteristics of the origin and decomposition degree of crop residues have also been reported to influence pesticide degradation (Rampoldi et al, 2008;Aslam et al, 2014).…”
Section: Introductionmentioning
confidence: 99%